2021
DOI: 10.1108/ijbm-08-2020-0414
|View full text |Cite
|
Sign up to set email alerts
|

How infomediaries on Twitter influence business outcomes of a bank

Abstract: PurposeThe purpose of this paper is to empirically explore under which conditions Tweets of infomediaries (i.e. ordinary users having few or no followers on Twitter) might nevertheless promote a negative sentiment toward a corporation to the point of having a negative impact on the corporation's outcomes.Design/methodology/approachThe empirical study is based on a unique database that combines a sample of one year of Twitter conversations about an Italian bank and its daily business performances (i.e. number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 52 publications
(63 reference statements)
0
19
0
Order By: Relevance
“…However, their expressed judgments give birth to plural and unaggregated conversations (Schultz, Castelló, & Morsing, 2013). Recent research has shown that judgments posted by individuals on social media can nevertheless become central in bridging conversations, as they give the impression that these are part of a larger conversation, thereby potentially impacting business outcomes (Illia, et al, 2021). As we will argue next, it is the bridging of such propriety judgments at the meso-level which eventually enables propriety judgments to influence validity judgments expressed by news media.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
See 3 more Smart Citations
“…However, their expressed judgments give birth to plural and unaggregated conversations (Schultz, Castelló, & Morsing, 2013). Recent research has shown that judgments posted by individuals on social media can nevertheless become central in bridging conversations, as they give the impression that these are part of a larger conversation, thereby potentially impacting business outcomes (Illia, et al, 2021). As we will argue next, it is the bridging of such propriety judgments at the meso-level which eventually enables propriety judgments to influence validity judgments expressed by news media.…”
Section: Theoretical Frameworkmentioning
confidence: 96%
“…Indeed, social media have become a vehicle, where propriety judgments become increasingly expressed by diverse actors (Etter et al, 2018(Etter et al, , 2019Wang, Reger, & Pfarrer, 2021). More importantly, through the expression of individual judgments, other individuals may be encouraged to similarly express theirs, accumulating to generate substantive contestation of organizations (Albu & Etter, 2016;Illia et al, 2021). This becomes particularly important when individuals harbor beliefs that their personal judgment deviates from an assumed majority opinion, which inhibits them from expressing their propriety judgments (Bitektine & Haack, 2015;Clemente & Roulet, 2015).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…After this procedure, the sample contained 149,366 tweets. Then we selected those tweets that were crucial to create volume of conversations, and specifically those tweets that were central in the networked conversations in terms of bridging and retweeting power on a weekly basis (Illia, Colleoni, & Meggiorin, 2021). After this, we ended up with a total of 3513 tweets that were core for the emergence of network of conversations in the 13 weeks from January to April 2017.…”
Section: Databasementioning
confidence: 99%